The clinical Pseudomonas fluorescens MFN1032 strain exerts a cytotoxic effect on epithelial intestinal cells and induces Interleukin-8 via the AP-1 signaling pathway - Madi, Amar (BioMed Central, 2010)
BACKGROUND: Pseudomonas fluorescens is present in low number in the intestinal lumen and has been proposed to play a role in Crohn's disease (CD). Indeed, a highly specific antigen, I2, has been detected in CD patients and correlated to the severity of the disease. We aimed to determine whether P. fluorescens was able to adhere to human intestinal epithelial cells (IECs), induce cytotoxicity and activate a proinflammatory response. RESULTS: Behaviour of the clinical strain P. fluorescens MFN1032 was compared to that of the psychrotrophic strain P. fluorescens MF37 and the opportunistic pathogen P. aeruginosa PAO1. Both strains of P. fluorescens were found to adhere on Caco-2/TC7 and HT-29 cells. Their cytotoxicity towards these two cell lines determined by LDH release assays was dose-dependent and higher for the clinical strain MFN1032 than for MF37 but lower than P. aeruginosa PAO1. The two strains of P. fluorescens also induced IL-8 secretion by Caco-2/TC7 and HT-29 cells via the AP-1 signaling pathway whereas P. aeruginosa PAO1 potentially used the NF-κB pathway. CONCLUSIONS: The present work shows, for the first time, that P. fluorescens MFN1032 is able to adhere to IECs, exert cytotoxic effects and induce a proinflammatory reaction. Our results are consistent with a possible contribution of P. fluorescens in CD and could explain the presence of specific antibodies against this bacterium in the blood of patients.